News Consumption Behavior of Generation Z In The Reading Community Via Instagram - Dian Andriany; Ike Junita Triwardhani (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This research study examines the impact of the post-truth era—where emotional responses, personal beliefs, and subjective interpretations are more influential than objective facts—on Generation Z's news consumption patterns, particularly in the context of social media. The objective of this study is to examine and assess Generation Z's news consumption patterns in the context of the social media platform Instagram. Data was collected through semi-structured interviews, observational studies, and a comprehensive review of relevant literature. The purposive selection of respondents included individuals from Generation Z who actively use Instagram, with a minimum age of 17.The study's findings suggest that Generation Z's news consumption habits are influenced by the prevalence of easily accessible social media platforms, as well as trends and influencers in this space. While respondents demonstrated an understanding of the potential risks associated with fake news, they frequently encountered challenges in verifying the reliability of the content they encountered. This underscores the necessity for strategies aimed at promoting news literacy. The study found that trust in news sources was influenced by the reputation of the media outlet, the visual appeal of the content, and the opinions of their social networks. The study's findings underscore the pervasive influence of prevailing trends, prominent influencers, and the ease of access to information, particularly through social media platforms, on Generation Z's news consumption patterns. While respondents acknowledged the dangers associated with fake news, their inclination to verify information remains a significant challenge.